Migration and the Making of the English Middle Class - Vasiliki Fouka; Theo Serlin (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
When do people identify with their class? Evidence from social psychology shows that individuals are more likely to identify with a group if they are similar to its members. We study early 20th century Britain and show that regional cultural heterogeneity combined with internal migration influenced class identity. We develop and validate a measure of class identity using naming decisions. Exploiting within-household variation, we show that migration patterns that increased the local share of culturally-distant workers reduced working class identification. Where migration increased the cultural distance of the working class, workers were less likely to join unions, voters were less likely to support the nascent Labour Party, and parliamentary candidates were less likely to target working class voters. By 1911, slower in-migration and rising local population growth reduced working class distance in urban areas, which also became strongholds of support for Labour. Migration alters social identity and creates political cleavages.
Keywords: D72; J61; N33; Z10; 330; migration; identity; class